Investigation of Valence Mixing in Sodium-Ion Battery Cathode Material Prussian White by Mössbauer Spectroscopy - Ericsson, Tore; Häggström, Lennart; Ojwang, Dickson O.; Brant, William R. (Frontiers in Energy Research, 2022)
Prussian white (PW), Na2Fe[Fe(CN)6], with a high theoretical capacity of 170 mAhg-1 and low-cost synthesis is a highly attractive cathode material for sustainable sodium-ion batteries. However, there exists significant variability in the reported electrochemical performance. This variability has its roots in the compositional flexibility possible for all Prussian blue analogues and is exasperated by the difficulty of accurately quantifying the composition of PW specifically. This work presents a means of accurately quantifying vacancy content, valence distribution and consequently overall composition via Mössbauer spectroscopy. PW cathodes with three different sodium contents were investigated at 295 K and 90 K. The observation of only two iron environments for the fully sodiated compound indicated the absence of [FeCN)6]4- vacancies. Due to intervalence charge-transfer between iron centers at 295 K, accurate determination of valences was not possible. However, by observing the trend of spectral intensities and center shift for the nitrogen bound and carbon bound iron respectively at 90 K, valence mixing between the iron sites could be quantified. By accounting for valence mixing, the sum of iron valences agreed with the sodium content determined from elemental analysis. Without agreement between the total valence sum and measured composition there exists uncertainty around the accuracy of the elemental analysis and vacancy content determination. Thus, this study offers one more stepping-stone towards a more rigorous characterization of composition in PW enabling the continued optimization for battery applications. More broadly, the approach is valuable for characterizing iron based PBAs in applications where precise composition and valence determination and control is desired.